2018
DOI: 10.1371/journal.pone.0209932
|View full text |Cite
|
Sign up to set email alerts
|

Delay in treatment initiation and treatment outcomes among adult patients with multidrug-resistant tuberculosis at Yangon Regional Tuberculosis Centre, Myanmar: A retrospective study

Abstract: BackgroundMyanmar faces a health security threat, with an increasing number of multidrug-resistant tuberculosis (MDR-TB) cases. Long delays in the initiation of treatment are a barrier to MDR-TB control.ObjectivesThe main objectives of this study were (1) to identify the determinants of delay in treatment initiation after MDR-TB diagnosis, and (2) to explore the effects of treatment delay on disease infectivity, severity, treatment adherence, and treatment outcomes.MethodsThis retrospective study reviewed 330 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 18 publications
3
34
2
2
Order By: Relevance
“…As the evidence showed that those smear-positive patients were more infectious and their probability of infectiousness increases with increased sputum smear grading [12]. High sputum smear grading was established as a result of long treatment delay which will also directly linked to extensive transmission to the communities because of large MTB load and prolonged contacts [13]. Study results from Ethiopia, China, Vietnam, and India evidenced that high smear grading was also associated with delayed smear and culture conversion, longer isolation period, more intensive treatment, and poor interim and nal treatment outcomes [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…As the evidence showed that those smear-positive patients were more infectious and their probability of infectiousness increases with increased sputum smear grading [12]. High sputum smear grading was established as a result of long treatment delay which will also directly linked to extensive transmission to the communities because of large MTB load and prolonged contacts [13]. Study results from Ethiopia, China, Vietnam, and India evidenced that high smear grading was also associated with delayed smear and culture conversion, longer isolation period, more intensive treatment, and poor interim and nal treatment outcomes [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Delayed diagnosis and treatment of TB led to severe clinical disease and drug resistance [21, 22]. A time-period of > 60 days from the onset of TB symptoms to start of anti-TB treatment is associated with unfavorable treatment outcomes, including treatment failure and mortality in Ethiopia [23].…”
Section: Discussionmentioning
confidence: 99%
“…Given these requirements, it is not surprising that later Pali commentaries and recensions, as recorded for instance in the ‘Extended Mahāvaṃsa ’, 18 specify that in fact each Asokan mission consisted of a leader and four other associates in order to form a minimum chapter of five monks 19 . Modern Mon-Burmese chronicles even provide the names of the three additional missionary monks travelling together with Soṇa and Uttara, namely “Aniruddha, Tissakutta and Somarasa who arrived in Sudhammavatī [Thaton]” (Tun Aung Chain 2010: 13) 20 . Conversely, a recent Thai chronicle or tamnan composed in the twentieth century assigns them different names of “Phra Chaniya, Phra Phuriya and Phra Muniya” (Thammathatto and Pho Na Pramuanmark 1989: 55, 69) 21 .…”
Section: Buddhist Legends and Historical ‘Truth’mentioning
confidence: 99%
“…On the one hand, the Mon-Burmese, basing their arguments mainly on later chronicles (e.g. Bode 1897: 10–11; Tun Aung Chain 2010) and strong local and oral traditions, generally locate it in lower Burma. It seems fair to say from the Kalyāṇī inscriptions that the myth of Suvaṇṇabhūmi there actually dates to at least about the middle of the second millennium AD.…”
Section: How Many Golden Lands?mentioning
confidence: 99%
See 1 more Smart Citation